Hormonal control of human colon carcinoma cell growth in serum-free medium. - Murakami, H (1980)
A human colon carcinoma cell line, HC84S, was established in serum-supplemented medium from a colon tumor line T84 transplanted in nude mice. These cells also grew in a serum-free, synthetic medium supplement with insulin, glucagon, epidermal growth factor, transferrin, hydrocortisone, triiodothyronine, selenium, and ascorbic acid. HC84S cells grew 3 times faster in this medium than in serum-containing medium and formed gland-like structures closely resembling the original tumor morphologically. In serum-containing medium, the cells grew as a monolayer and did not form such structures. Primary cultures from transplantable human colon tumor lines maintained in nude mice and a primary tumor from a patient were established directly in this hormone-supplemented medium in collagen-treated plastic dishes without fibroblast overgrowth. The hormone-supplemented medium may be generally useful for the establishment of human colon carcinoma cell lines.